Capacity Building on BSB Organic Development Center - Winarko, Hilarius Bambang; Fitriningrum, Andriati; Wahyuni, Maria Josef Retno Budi; Pulungan, Andrey Hasiholan (Journal of Community Services: Sustainability and Empowerment, 2021)
This community service project was aimed to scale up Bina Sarana Bhakti (BSB) organic development center’s management with two-day workshops. BSB needs to improve its managerial skills and knowledge in-order able to transform its business in a more profitable way. Agile leadership with good communication approach and human capital plays important role in-order BSB able to keep in the right track and sustainable in facing fierced market competitions and future uncertainty.